Identification of potential gene‐associated major traits using GBS‐GWAS for Korean apple germplasm collections. (8th November 2017) - Lee, So Jin; Ban, Seung Hyun; Kim, Gi Hoon; Kwon, Soon Il; Kim, Jeong Hee; Choi, Cheol
Abstract: Genomewide association study (GWAS), which queries the association between loci and a particular trait by examining single nucleotide polymorphisms (SNPs) of the entire genome, is used in many fields of study. The development of next‐generation sequencing techniques has facilitated GWASs by decreasing the sequencing costs and time. In particular, genotyping by sequencing (GBS) is useful for sequencing many samples simultaneously and at a moderate price. Herein, we describe a potential GWAS using GBS, focused on the apple germplasm, with the goal of developing an effective apple breeding strategy through the identification of useful markers. From 308 Korean apple germplasm, SNPs were selected after GBS, and major traits were investigated. Proprietary individuals were confirmed and grouped by association through genetic diversity and population structure analyses of the selected SNPs. Genes highly associated with the target traits were identified, respectively. As the first GWAS report on the apple germplasm, these results will be useful as base data for GWASs on other apple populations and traits.